The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1088/1674-1056/28/7/074209
|View full text |Cite
|
Sign up to set email alerts
|

Phase-related noise characteristics of 780 nm band single-frequency lasers used in the cold atomic clock*

Abstract: We propose a method to directly measure phase-related noise characteristics of single-frequency lasers in the 728–980 nm band based on a 120° phase difference interferometer. Differential phase information of the laser under test is demodulated via the interferometer. Other parameters related to the phase noise characteristics such as linewidth at different observation time, phase/frequency noise, power spectrum density of phase/frequency fluctuation, and Allan deviation are further obtained. Frequency noise a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…[1,2] Especially, the deep-UV lasers with narrow-linewidth (< 10 GHz) can improve the effect significantly for the abovementioned applications. [3,4] So far, using narrow-linewidth solid-state lasers as fundamental frequency sources for frequency conversion, has been the most popular method to produce UV lasers. [5][6][7][8][9][10][11][12][13][14] In addition, narrow-linewidth fiber lasers are also potential fundamental frequency sources, which can provide better-quality beams, improved compactness, higher stability and efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] Especially, the deep-UV lasers with narrow-linewidth (< 10 GHz) can improve the effect significantly for the abovementioned applications. [3,4] So far, using narrow-linewidth solid-state lasers as fundamental frequency sources for frequency conversion, has been the most popular method to produce UV lasers. [5][6][7][8][9][10][11][12][13][14] In addition, narrow-linewidth fiber lasers are also potential fundamental frequency sources, which can provide better-quality beams, improved compactness, higher stability and efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Single-frequency fiber lasers operating at ∼ 2 µm have attracted intense attention for their wide-ranging applications, from high-resolution spectroscopy and noninvasive medicine to coherent beam combining, due to their outstanding properties of low noise, narrow linewidth and at an eye-safe wavelength regime. [1][2][3][4] Up to now, ∼ 2 µm single-frequency fiber lasers have been achieved in various cavity structures, including ring cavities, distributed feedback (DFB) cavities and distributed Bragg reflector (DBR) cavities. [5][6][7] More recently, Walasik et al reported a 2 µm single-frequency all-fiber DFB laser source employing fiber Bragg gratings (FBGs) which has a laser linewidth of 5 kHz.…”
Section: Introductionmentioning
confidence: 99%